2001
DOI: 10.1212/wnl.56.7.906
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of glutamate and GABA-A receptor subunit mRNA in cortical dysplasia

Abstract: Differential expression of GluR, NR, and GABA(A)R mRNA in dysplastic and heterotopic neurons demonstrates cell specific gene transcription changes in focal cortical dysplasia. These results suggest that dysplastic and heterotopic neurons may be pharmacologically distinct and make differential contributions epileptogenesis in focal cortical dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 37 publications
0
121
2
2
Order By: Relevance
“…Studies performed in humans and other animal models have implicated disruptions in the GABAergic system in seizure activity. These disruptions include altered inhibitory drive (Smith et al, 1999;Zhu and Roper, 2000;Calcagnotto et al, 2002), alterations in GABA interneuron populations (Ferrer et al, 1994;Mathern et al, 1995;Jacobs et al, 1996;Marco et al, 1996;Hablitz and DeFazio, 1998;Rosen et al, 1998;Spreafico et al, 1998;Roper et al, 1999;Schwarz et al, 2000), changes in GABA A receptor subunits (DeFazio and Hablitz, 1999;Loup et al, 2000;Redecker et al, 2000;Coulter, 2001;Crino et al, 2001;White et al, 2001;Palma et al, 2005), and changes in GABA reuptake transporters (Calcagnotto et al, 2002(Calcagnotto et al, , 2005). An important remaining question is what events precipitate the onset of seizures against this background of reduced inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in humans and other animal models have implicated disruptions in the GABAergic system in seizure activity. These disruptions include altered inhibitory drive (Smith et al, 1999;Zhu and Roper, 2000;Calcagnotto et al, 2002), alterations in GABA interneuron populations (Ferrer et al, 1994;Mathern et al, 1995;Jacobs et al, 1996;Marco et al, 1996;Hablitz and DeFazio, 1998;Rosen et al, 1998;Spreafico et al, 1998;Roper et al, 1999;Schwarz et al, 2000), changes in GABA A receptor subunits (DeFazio and Hablitz, 1999;Loup et al, 2000;Redecker et al, 2000;Coulter, 2001;Crino et al, 2001;White et al, 2001;Palma et al, 2005), and changes in GABA reuptake transporters (Calcagnotto et al, 2002(Calcagnotto et al, , 2005). An important remaining question is what events precipitate the onset of seizures against this background of reduced inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been implemented in human and experimental epilepsy models and in live, as well as fixed, cell types (10)(11)(12)(13). The use of an oligo-dT primer and T7 RNA polymerase permits amplification of a broad population of expressed genes across many gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Among the iGluRs, the role of N-methyl-Daspartate (NMDA) receptors (GluN) in cortical hyperexcitability has received considerable attention. Several studies have shown alteration in GluN subunit expression in human epileptic tissue with increased expression of the subunit NR2B [149][150][151][152]. Changes in the expression of components of the membrane-associated guanylate kinase (MAGUK) protein family, interacting with GluN, has been also reported [153,154].…”
Section: Epileptogenesismentioning
confidence: 99%
“…In particular, recent data showing upregulation of NMDA regulatory subunits and related MAGUK proteins in epileptogenic/dysplastic areas suggest that glutamate/NMDA/ MAGUK dysregulation might also represent the intracellular trigger that modifies brain morphology and induces cell death [154]. Alteration in the expression of α-amino-3-hydroxy-5-methyl-4-isixazolepropionic acid receptor subtypes has been also reported ( [150]; for reviews see [146] and [147]). In addition to the deregulation of iGluR, the cellular distribution of mGluR subtypes, with high expression of mGluR1α and mGluR5 in dysmorphic neurons, suggests a possible contribution of group I mGluRs to the intrinsic and high epileptogenicity of dysplastic cortical regions [155].…”
Section: Epileptogenesismentioning
confidence: 99%